Instructional Material Development for Vocabulary Enhancement of Grade 9 Students of Botolan National High School - Bellido, Willyn A.; Rico, Felipa M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
This study aimed to determine the level of vocabulary skills of Grade 9 students of Botolan National High. This was identified by using the DepEd E-class Record transmutation table and descriptive rating. The study which used descriptive analysis research was also utilized to know the level of vocabulary of 155 Grade 9 respondents of Botolan National High School SY 2019- 2020. Results and findings of the study led to the development of the supplementary instructional materials to enhance the level of vocabulary of Grade 9 students. The findings revealed that the level of vocabulary skills of the students before exposure to context clues was Fairly Satisfactory, while the level of the vocabulary skills of the students after exposure to context clues was Satisfactory. The level of vocabulary skills of the students before exposure to visual association was Fairly Satisfactory while the level of the vocabulary skills of the students after exposure to visual association was also Fairly Satisfactory. There was significant relationship on the level of vocabulary skills of the students before and after exposure to context clue and visual association strategies. It is recommended therefore that appropriate supplementary instructional materials be devised and utilized in order to enhance the level of vocabulary skills of Grade 9 students.